Clinical availability of SNOOP4 in acute non-traumatic headache patients admitted to the emergency department - Wachira Wongtanasarasin (2020)
© The Author(s) 2020. Objectives: Non-traumatic headache accounts for up to 4.5% of all patients presenting to the emergency department. Non-traumatic headache is generally classified into two categories: primary and secondary headache disorders. Differentiating secondary from primary headache disorders is essential. SNOOP4 is known as a mnemonic for suggesting clinicians send neuroimaging to rule out serious conditions. Yet, the benefit of using this mnemonic in the emergency department is not well established. This study aimed to assess the significance of SNOOP4 in detecting serious causes of non-traumatic headache in adults presenting to the emergency department. Methods: We conducted a prospective observational study of adult patients presenting to the emergency department of the single tertiary hospital over a period of 12 months. Patients with acute non-traumatic headache presented at the emergency department were included. A standard record form was used. Patients were investigated and treated following the pre-existing protocols. Results were interpreted by attending radiologists. Each factor, according to SNOOP4, was then evaluated for the ability to predict serious causes of non-traumatic headache. Results: A total of 90 patients were included in this study with complete details obtained on 83 (92.2%) patients. Of these, 63 (75.9%) were female. The mean age was 44.5 years (inter-quartile range: 27–58.5). The duration of the headache ranged from 10 min to 7 days. Out of 83, 27 (32.5%) had at least one SNOOP4 criterion. In all, 25 patients (30.1%) underwent neuroimaging. The sensitivity, specificity, positive predictive value, and negative predictive value of SNOOP4 were 77.8%, 73.0%, 25.9%, and 96.4% respectively. Conclusion: SNOOP4 criteria show very high negative predictive value for excluding serious causes of acute non-traumatic headache in adult patients presenting to the emergency department.